2017
DOI: 10.1016/j.cma.2017.03.036
|View full text |Cite
|
Sign up to set email alerts
|

A predictive framework to elucidate venous stenosis: CFD & shape optimization

Abstract: The surgical creation of vascular accesses for renal failure patients provides an abnormally high flow rate conduit in the patient’s upper arm vasculature that facilitates the hemodialysis treatment. These vascular accesses, however, are very often associated with complications that lead to access failure and thrombotic incidents, mainly due to excessive neointimal hyperplasia (NH) and subsequently stenosis. Development of a framework to monitor and predict the evolution of the venous system post access creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 62 publications
(52 reference statements)
1
4
0
Order By: Relevance
“…WSS results for this patient show that values are not restored to the pre-creation baseline set point as previously suggested (Javid Mahmoudzadeh Akherat et al 2017), but fluctuate around a new, higher value. This demonstrates a possible control mechanism in which the diameter is adjusted to maintain WSS within a narrow range of the new set point.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…WSS results for this patient show that values are not restored to the pre-creation baseline set point as previously suggested (Javid Mahmoudzadeh Akherat et al 2017), but fluctuate around a new, higher value. This demonstrates a possible control mechanism in which the diameter is adjusted to maintain WSS within a narrow range of the new set point.…”
Section: Discussionsupporting
confidence: 60%
“…Studies to monitor newly created AVFs have reported elevated WSS in the artery when compared to baseline (precreation) values (Ene-Iordache et al 2003). It would follow that the artery will increase in lumen diameter to lower the WSS back to baseline, which has been a hypothesis of previous AVF studies (Javid Mahmoudzadeh Akherat et al 2017). It is generally accepted that arterial vasculature seeks to maintain constant WSS at a preferred, homeostatic value (Humphrey 2008), with the presence of a control mechanism demonstrated by Le Noble et al (2005).…”
Section: Introductionmentioning
confidence: 98%
“…[22] On the other hand, the variation in vessel wall parameters increases turbulence and introduces ow separation, leading to damage repair and reconstruction of the endothelial cell. [27] Therefore, the hemorrhagic presentation in AVMs may result from the interaction of hemodynamics and speci c angioarchitecture resulting in occlusive congestion within the AVM nidus. [9] There were some limitations in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The hemodynamic characteristics associated with a stenosis in an artery are 1) pre-stenotic pressure buildup and 2) post-stenotic pressure drop [5, 6]. When pressure waves pass through an inflow stenosis, the pressure energy is dissipated by being converted to kinetic energy and is attenuated downstream to the anastomosis along the length of an AVF according to Poiseuille’s law.…”
Section: Methodsmentioning
confidence: 99%